Guide to commodity price forecasting - Commodity Research Bureau (U.S.); Jiler, Harry; Parker, George B. (New York, 1965)
This book is on price trend and background data for commodity traded on all future markets.
oo 09/04/2019
Loans
Keywords: Agricultural prices; Produce trade